Brand supportive behaviour among insurance agents in the northern region of Malaysia - Adilah, Othman (2021)
Brand supportive behaviour is important to companies because it shows the willingness of agents to go beyond their prescribed roles for the good of the corporate brand. Hence, this study aimed to examine the influence of internal brand orientation and customer orientation on brand supportive behaviour with the mediating role of brand psychological ownership. A research framework was established based on existing literature to test the relationship among these variables. The Social Exchange Theory and the Social Identity Theory were employed to explain the relationship between the variables being studied. In order to empirically test the research framework of the study, data were collected by employing a questionnaire survey. 350 respondents from the insurance industry were selected using the systematic sampling. The data collected was analysed using the Partial Least Square Structural Equation Modelling (PLS-SEM). The empirical result revealed that internal brand orientation, customer orientation, and brand psychological ownership influenced brand supportive behavior. In addition, it was also found that brand psychological ownership mediated the relationship between internal brand orientation and customer orientation with brand supportive behavior. The results of this study provides insights to managers whereby they must use appropriate applications of internal brand management practices such as internal brand orientation and customer orientation. These findings also suggest that internal brand orientation, customer orientation and brand psychological ownership are crucial factors that affect the willingness of agents to commit to brand supportive behavior.